2008
DOI: 10.1038/sc.2008.160
|View full text |Cite
|
Sign up to set email alerts
|

Activities of daily living performed by individuals with SCI: relationships with physical fitness and leisure time physical activity

Abstract: Study Design: Cross-sectional. Objectives: To examine patterns of participation in activities of daily living (ADL) and fitness-related factors associated with these patterns among individuals with spinal cord injury (SCI). Setting: Centre for Health Promotion and Rehabilitation at McMaster University, School of Kinesiology and Health Studies at Queen's University. Methods: Forty-eight participants completed the Physical Activity Recall Assessment for People with Spinal Cord Injury (PARA-SCI) and a fitness tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 19 publications
2
26
1
Order By: Relevance
“…The PARA-SCI is an interview tool organized around recall of activities undertaken during the 3 previous days, yielding scores for cumulative activity, leisure-time activity, and lifestyle activity. The reliability and validity of the tool have been demonstrated by the developers in recent years [27][28][29]. Limitations of the PARA-SCI include limited use by investigators beyond the developers, emphasis on physical activity, exclusion of subjective appraisals, and the technical complexity of interview administration.…”
Section: Activities Of Daily Living Measuresmentioning
confidence: 99%
“…The PARA-SCI is an interview tool organized around recall of activities undertaken during the 3 previous days, yielding scores for cumulative activity, leisure-time activity, and lifestyle activity. The reliability and validity of the tool have been demonstrated by the developers in recent years [27][28][29]. Limitations of the PARA-SCI include limited use by investigators beyond the developers, emphasis on physical activity, exclusion of subjective appraisals, and the technical complexity of interview administration.…”
Section: Activities Of Daily Living Measuresmentioning
confidence: 99%
“…For example, certain ADLs such as wheeling or cleaning may not be as intense or time-consuming for participants with greater function. With respect to ADLs, Hetz et al 10 found that individuals with tetraplegia reported spending twice as much time toileting and dressing when compared with people with paraplegia. As such, it is possible that participants with greater function report a similar amount of time spent in VLPA/inactivity when compared with participants with less function because they are more efficient with their ADLs and have more time to spend in LTPA, as well as VLPA/inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, emerging literature concerning ADLs suggests that women spend more time on specific activities, such as preparing meals and cleaning, when compared with men. 10 Thus, the lack of association between sex and VLPA/inactivity may be due to the different types of physical activities pursued. Past research supports an association between injury severity, mode of mobility and LTPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relation has also been studied in persons with a SCI. [5][6][7][8][9][10][11] However, these studies all used questionnaires to determine physical activity level. Although studies have shown that when using questionnaires there is a risk of overestimation and that self-reported activity level is only weakly related to objectively measured activity level.…”
Section: Introductionmentioning
confidence: 99%